CONTENT AND VISUAL ANALYSIS ON SHORT FILM: OLAK - Ni Putu Anggie Kusuma Wardhani; Putu Mayra Elkie Shafira; Putu Chrisma Dewi; Putu Chris Susanto (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2022)
ABSTRACTThe purpose of this study is to examine a short film in terms of content and visuals. Even though a film is of short duration, it does not deny that there are many things that can be analyzed, including the content and visuals in the short film. The authors analyzed the Indonesian short film titled “Olak”, directed by Wishnu Hazmi Lazuardi (2018). This study uses a non-participant descriptive qualitative method, analyzing existing data from sources on the internet without direct contact with the participants that are included in the data. The authors analyzed this short film in the context of its content and visual appearance, particularly commenting on the significance of repeating the same scene in a time loop—as a commentary of the dynamics that occur in everyday lives of typical Indonesian teenagers.Keywords: short film, content analysis, visual analysis, social dynamics, teenage film.